Facial Feminization: Systematic Review of the Literature. Issue 6 (June 2016) - Morrison, Shane D.; Vyas, Krishna S.; Motakef, Saba; Gast, Katherine M.; Chung, Michael T.; Rashidi, Vania; Satterwhite, Thomas; Kuzon, William; Cederna, Paul S.
Abstract : Background: Facial feminization surgery encompasses a broad range of craniomaxillofacial surgical procedures designed to change masculine facial features into feminine features. The surgical principles of facial feminization surgery can be applied to male-to-female transsexuals and anyone desiring feminization of the face. Although the prevalence of these procedures is difficult to quantify, because of the rising prevalence of transgenderism (approximately one in 14, 000 men) along with improved insurance coverage for gender-confirming surgery, surgeons versed in techniques, outcomes, and challenges of facial feminization surgery are needed. This review is designed to critically appraise the current facial feminization surgery literature. Methods: A comprehensive literature search of the Medline, PubMed, and EMBASE databases was conducted for studies published through October of 2014 with multiple search terms related to facial feminization. Data on techniques, outcomes, complications, and patient satisfaction were collected. Results: Fifteen articles were selected and reviewed from the 24 identified, all of which were either retrospective or case series/reports. Articles covered a variety of facial feminization procedures. A total of 1121 patients underwent facial feminization surgery, with seven complications reported, although many articles did not explicitly comment on complications. Satisfaction was high, although most studies did not use validated or quantified approaches to address satisfaction. Conclusions: Facial feminization surgery appears to be safe and satisfactory for patients. Further studies are required to better compare different techniques to more robustly establish best practices. Prospective studies and patient-reported outcomes are needed to establish quality-of-life outcomes for patients. However, based on these studies, it appears that facial feminization surgery is highly efficacious and beneficial to patients. Abstract : Video Discussion by Jeffrey H. Spiegel, M.D., is Available Online for this Article.